Research on Design, Construction and Maintenance Technology of Advanced Marine Research Ship. Issue 2 (March 2021) - Gong, Qiyong; Zhan, Jun; Wang, Pengzhi; Nie, Xin; Zhao, Lei; Shen, Xing
Abstract: In response to my country's future planning for the design and construction of a new round of marine scientific research ships, the types, functions and layout areas of special equipment are subdivided to classify and explore the key points of special equipment installation and control for marine scientific research ships, and finally become more systematic Formed the installation control elements of various special equipment. Combining previous production design and construction experience of scientific research ships, the article focuses on the scientific layout of survey equipment, optimized design of cabin clear height, reasonable layout of laboratory equipment and related pipelines, vibration and noise reduction, electromagnetic compatibility, and modular design. On the other hand, analyse the key points of the comprehensive layout optimization design of the scientific research ship for reference for subsequent production design of the scientific research ship. Together with the experience and concepts of the shipyard, the comprehensive layout of the scientific research ship can be further improved, and the on-site construction modification can be reduced, thereby promoting domestic the construction quality of scientific research ships has improved to a new level, reaching the international leading level in all aspects.